Evaluation of the heat transfer enhancement during pool boiling using low concentrations of Al2O3-water based nanofluid - Manetti, Leonardo Lachi [UNESP] (2017)
This study presents experimental results for the heat transfer coefficient during pool boiling of DI water and Al2O3-water based nanofluid at saturation conditions. Based on these data, an analysis of the heat transfer enhancement due to the nanofluids was performed. The experiments were performed for Al2O3-water based nanofluid with different volume concentrations (0.0007 vol.% and 0.007 vol.%, corresponding to low and high nanofluid concentration, respectively). A copper surface, with different roughness values (Ra = 0.05 μm, corresponding to a smooth surface, and Ra = 0.23 μm, corresponding to a rough surface), was used as test section. The nanoparticle average size was 10 nm and the applied heat flux ranged from 100 to 800 kW/m2. For nanofluid pool boiling, it was observed an increase in the heat transfer coefficient up to 75 %, and 15% for the smooth and rough surfaces, respectively, in comparison to that of DI water. According to results, the surface roughness is strongly affected by nanofluid concentration due to the nanoparticle deposition on the heating surface. The results indicate that the use of nanofluids is effective on pool boiling heat transfer, for moderate heat flux and low volumetric concentration.